Photodynamic activity of tetraazachlorin derivate studied in vivo - V. I. Ivanova-Radkevich; Е. А. Machinskaya (Biomedical Photonics)
The results of investigation for photodynamic activity of new tetraazachlorin derivate – tetramethyltribenzotetraazachlorin, synthesized in Research Institute of Organic Intermediates and Dyes. The study was performed on female mice of СВА line. The tumor model was transferred solid ascetic sarcoma S-37. The samples of photosensitizer, previously solubilized in 10% aqueou s solution ofCremophor EL, injected to mice intravenously on the 7th day of tumor growth in dose of 1–2 mg/kg. Two hours later the irradiation of sensitized tumor using light emitting diode device in a maximal wavelength of 755 nm (light power density – 50 mW/cm2, maximal total light dose – 300 J/cm2) was performed. The efficacy of photodynamic therapy was assessed by growth inhibition rates in the study group comparing with control group. The study showed that photodynamic therapy with investigated sample in dose of 2 mg/kg and light dose of 300 J/cm2 significantly inhibited the tumor growth (inhibition rate of 70–80% within 20 days), indicating prospectivity of subsequent investigations of tetraazachlorin as photosensitizer for photodynamic therapy of malignant tumors.